Chemical photocatalysis - König, Burkhard (Walter de Gruyter GmbH & Co. KG, 2013)
Visible light is an abundant source of energy. While the conversion of light energy into electrical energy (photovoltaics) is highly developed and commercialized, the use of visible light in chemical synthesis is far less explored. Chemical photocatalysts that mimic principles of biological photosynthesis utilize visible light to drive endothermic or kinetically hindered reactions. This work summarizes in 16 chapters the state of the art and the challenges of this emerging future technology.